Phytoplankton growth characterization in short term MPN culture assays using 18S metabarcoding and qRT-PCR. (1st November 2019) - Petri, Brian; Chaganti, Subba Rao; Chan, Po-Shun; Heath, Daniel
Abstract: The most probable number dilution-culture assay (MPN) is used to enumerate viable phytoplankton in regulatory tests of ballast water treatment systems. However the United States Coast Guard has not yet accepted MPN, in part due to concerns of biased results due to cells being viable but not growing. MPN does not assess the fate of every cell, and thus the bias can only be evaluated by a companion method that assesses the ability of the various taxa to grow. This growth ability ("growability") is the complement of the bias, and has been evaluated by microscopic taxonomy of before-culture and after-culture samples. However, microscopic taxonomy is extremely laborious and few data have been produced for phytoplankton growability in MPN assays. To address the need for more and more reliable growability data, a method was developed using next-generation sequencing (NGS) and quantitative real time PCR (qRT-PCR) techniques that target the V9 region of the 18S rRNA gene for the taxonomic identification and growth assessment of eukaryotic phytoplankton, respectively. This growability method was applied to MPN samples from a ballast water management system test that were incubated with two different enrichment media at two different temperatures. DNA was extracted from filters of before-culture and after-culture samples, and assessed for taxonomy by NGS and for PCR template DNA concentration by qRT-PCR. Growth ratios based on changes in 18S template concentration over the incubation period were calculated for each taxon, and dead-cell DNA persistence through a 14 day incubation was verified to be <1% and did not influence the growth calculations. In total, 95 of 97 eukaryotic phytoplankton in the before-culture sample demonstrated growth, with definitive growth ratios ranging from 4.0 × 10 1 –2.6 × 10 5 . An additional 13 taxa demonstrated growth from non-detect in before-culture samples. Taxa-based growability values were 87–88% in individual incubation conditions with no statistical differences among conditions, and 98% for all conditions combined. When growability was weighted by the before-culture abundance of each taxa, relevant to regulations based on all organisms regardless of taxa, community-based growability was >99% in each condition and in all conditions combined because the most abundant taxa all exhibited growth. This study verifies that conventional phytoplankton MPN assays produce accurate results with low bias from undetected viable cells, regardless of enrichments and incubation temperatures. This work can provide regulatory confidence for broader acceptance of MPN assays without limitations. Graphical abstract: Image 1 Highlights: Method developed to measure phytoplankton growability using genomic tools. Phytoplankton growability was 98% for taxa and >99% for community. No differences in growability between incubation media and temperatures. Majority of 10–50 μm organisms were phytoplankton. MPN used in ballast water management system testing is reliable and has low bias.